PENGARUH STATUS MIGRASI, PEKERJAAN, PENDIDIKAN, DAN LATAR BELAKANG EKONOMI TERHADAP UKP DAN FERTILITAS WANITA USIA SUBUR - Jayakusuma, I Made Wisnu; Sudibia, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to analyze 1) the effect of migration status, employment status, education level, and economic background on the age at first marriage of women of childbearing age in Badung Regency; 2) The effect of migration status, employment status, education level, economic background, and age at first marriage on the fertility of women of childbearing age in Badung Regency; 3) Indirect effect of migration status, employment status, education level, economic background, and age at first marriage on the fertility of women of childbearing age in Badung Regency. The data analysis technique used is descriptive statistics and inferential statistics consisting of path analysis and Sobel test. The results showed 1) Migrant women have a lower age at first marriage than non-migrant women, women who work in the informal sector have a lower age at first marriage than women who work in the formal sector, education level has a positive and significant effect on age at first marriage, while economic background has a negative and significant effect on age at first marriage; 2) Migrant women have a higher fertility rate than non-migrant women, women who work in the informal sector have a higher fertility rate than women who work in the formal sector, education level has a negative effect on fertility, while economic background has no significant effect on fertility, and age at first marriage has a negative effect on the fertility of women of childbearing age in Badung Regency; 3) Age at first marriage mediates the effect of employment status, education level, and economic background on fertility, but does not mediate the effect of migration status on fertility of women of childbearing age in Badung Regency.